BAS Photo Contest (The Biblical archaeology review, 1982)
Long after the memories of heat and discomfort have faded, participants in the Biblical Archaeology Society six-week Israel Summer Seminar will cherish their photographic records of the summer’s experiences and adventures. Upon their return to the United States, the Israel summer seminarians submitted their photographs and slides to the Biblical Archaeology Review photo contest. […]